Electrodynamic Sorting of Industrial Scrap Metal - James R. Nagel; Dave Cohrs; Jacob Salgado; Raj K. Rajamani (KONA Powder and Particle Journal, 2019)
Electrodynamic sorting (EDX) is a new technology developed to sort industrial scrap metals. Under the present embodiment, an electromagnet is placed directly underneath a conveyor belt and then excited by an alternating electrical current to produce a time-varying magnetic field. As scrap particles pass through the field overhead, electrical eddy currents are induced throughout their volumes and then repelled away. If the frequency of excitation is very high (e.g., 12 kHz), then the lightweight aluminum particles tend to jump far more dramatically than heavier materials like copper, brass, and zinc. To demonstrate the principle, a small-scale prototype was assembled and tested. Using an 8-inch (20 cm) lane width, the system could process industrial scrap Zorba at a throughput of over 550 lbs/hour (225 kg/h) with an aluminum grade of 97.6 % and a recovery of 93 %.